Essays on Transport Economics - Coto-Millán, Pablo; Inglada, Vicente; SpringerLink (Online service) (Heidelberg : Physica-Verlag HD : Imprint: Physica, 2007)
This book covers the basic analytical methods used in transportation economics and policy analysis. Encompassing fields of economics such as Industrial Organisation, Welfare Economics, General Equilibrium Theory and Input-Output-Analysis, the study of transport from an economic point of view serves as a test bench for applying the methodological developments of economic science to the real world. Each chapter begins with a brief theoretical introduction before evaluating case studies, using the most up-to-date statistical and econometric techniques. Discussed topics include technical and allocative efficiency and productivity related to transportation economics, the impact of information and communication technologies on transportation networks, competition and the effects of deregulation, uses of time and the effects of public investment on the economy and social welfare. The book is addressed to scientists and post-graduate students, but will also be of interest to professionals in civil and transport engineering.
Demand -- A Reassessment of the Characterisation of Congestion on an Urban Road Network — Some Theoretical Suggestions and Illustrative Experiments -- Estimation of the Economic Value of Student Urban Travel Time -- Price and Income Elasticities for Intercity Public Transport in Spain -- Supply and Efficiency -- Classifying Urban Passenger Transportation Services -- Analysis of the Allocative Efficiency in Public Firms: the Case of Railway -- The Effect of Using Aggregated Output in the Economic Analysis of Cargo Handling Operations -- Scale Economies, Elasticities of Substitution and Behaviour of the Railway Transport Costs in Spain -- Efficiency Stochastic Frontiers: a Panel Data Analysis for Spanish Airports (1992–1994) -- Multi-Output Analysis of the Costs and Productivity of Cargo Handling in Spanish Ports -- Market and Economic Impact Studies -- Economic Impact Study: Application to Ports -- Airport Management and Airline Competition in OECD Markets -- Dynamising Economic Impact Studies: the Case of the Port of Seville -- Valuation of Benefits and Costs -- Estimating the Economic Benefits of Bicycling and Bicycle Facilities: an Interpretive Review and Proposed Methods -- Valuation of Transport Externalities by Stated Choice Methods -- Externalities Analysis of Investments in Infrastructure: a Practical Approach -- Transportation Network and Information and Communications Technology -- ITS-Based Transport Concepts and Location Preference: Will ITS Change ‘Business as Usual’? -- The Economics of Transportation Network Growth -- Transport Network Development and the Location of Economic Activity -- Mapping the Terrain of Information and Communications Technology (ICT) and Household Travel.
Keywords: Entrepreneurship; Industrial organization; Regional economics; Spatial economics; Microeconomics; Entrepreneurship; Industrial Organization; Regional/Spatial Science; Microeconomics